Longitudinal effect of topical antiglaucoma medications on central corneal thickness. (5th June 2013) - Viswanathan, Deepa; Goldberg, Ivan; Graham, Stuart L
Abstract Background To determine the change in central corneal thickness over time and whether the use of long‐term topical antiglaucoma medications influences central corneal thickness. Design Case control study with retrospective and prospective data collection. Participants One hundred eighty‐seven eyes of 187 glaucoma patients (mean follow up 6.92 ± 1.67 years) being treated with topical antiglaucoma medications (at least 3 years) with no history of surgery or laser were included and compared with 100 eyes of 100 age–matched, untreated control subjects (mean follow up 6.58 ± 1.93 years) who were glaucoma suspects with normal intraocular pressure not on any treatment. Methods Demographic data, central corneal thickness and intraocular pressure were collected at initial glaucoma diagnosis and at most recent visit, and findings were compared between two groups. Main Outcome Measures Mean change in central corneal thickness in microns (μm). Results Central corneal thickness fell significantly (P < 0.0001) in treated eyes but not in control eyes (P = 0.18); mean central corneal thickness reduction was 12.29 ± 13.65 μm in treated eyes and 1.17 ± 8.75 μm in controls. Among treated eyes, central corneal thickness reduction was significant (P < 0.0001) in those treated with either prostaglandins or a combination of prostaglandin and beta‐blockers, while no significant reduction occurred in eyes treated with only beta‐blockers (P = 0.15) when compared with control eyes. Conclusions Prostaglandins appear to be associated with a small but significant central corneal thickness reduction over time. Serial central corneal thickness measurements might be helpful in glaucoma patients, particularly those on prostaglandins.